Religiusitas Sesolahan Sanghyang Grodog Pada Upacara Pengaci Sakral Di Lembongan - Ni Wayan Juli Artiningsih (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Sanghyang Grodog is one of the traditions that is still strong today in Pakraman Lembongan Village, Nusa Penida District. Sanghyang Grodog is a “village pengaci ritual” which is performed every pinanggl tilem sasih karo, with the function of being a “village supervisor”. Nyomia Desa is a ceremony performed to neutralize negative elements so that they become positive. Sanghyang Grodog is not as common as other Sanghyang dances in general in Bali. The difference is that the Sanghyang Grodog dance is not only sacred, this dance does not stop just as a dance, but is a perfect blend of rhythmic gending (audio singing, sound / sound), visual (form, form, visual), and agem (motion, kinetic). The number is also not only one or two but at the same time there are 23 types of Sanghyang which are then offered as sacred aci at Pakraman Lembongan Village for 11 consecutive days. The problems in this writing include; 1) what is the form of the Aci Sanghyang Grodog ceremony in Lembongan, 2) The religious aspects of the Aci Sanghyang Grodog ceremony in Lembongan, 3) what are the implications of religious values in the grodog sanghyang school in Lembongan. This writing aims to determine the religiosity at the Aci Sanghyang Grodog ceremony in Lembongan. The data analysis was performed using a qualitative descriptive method.